Concussion Experiences in New England Private Preparatory High School Students Who Played Sports or Recreational Activities. (5th May 2020) - Daugherty, Jill; Waltzman, Dana; Snedaker, Katherine P.; Bouton, Jason; Zhang, Xinjian; Wang, David
ABSTRACT: BACKGROUND: Sports‐ and recreation‐related (SRR) activities are a major cause of adolescent concussions. Most adolescent SRR concussion research has been conducted among public school students. As private schools are qualitatively different from public schools (eg, location, socioeconomic status, sports played), this study explores the concussion experiences of a large group of private high school students. METHODS: We surveyed 2047 New England private preparatory high school students who played sports or engaged in a recreational activity in 2018 about the sports they played, and their self‐reported concussion experiences (eg, age at first concussion, if concussions were sports‐ or recreation‐related). Descriptive, bivariate, and multivariate statistics are presented. RESULTS: One‐third (33.0%) of students who reported engaging in sport‐ or recreation‐related activities self‐reported experiencing a concussion in their lifetime. A higher percentage of boys, students who played contact sports, and those who played multiple seasons of school sports reported a concussion. Sex, contact level of primary sport played, and age of first concussion were also significantly associated with reporting a sports‐ or recreation‐related concussion. CONCLUSIONS: A sizeable proportion of private preparatory high school students reported experiencing a concussion, with some students at higher risk. Private preparatory high school‐specific concussion prevention strategies may be needed.